Heroes from Alexander the Great and Julius Caesar to Churchill and de Gaulle - Johnson, Paul (Blackstone, 2007)
In this enlightening and entertaining work, Paul Johnson continues his engaging history series. As he has done in previous books, he approaches the subject of heroism by example. Here are men and women from every age, walk of life, and corner of the world who have inspired and transformed their cultures and the world itself. Heroes includes: Samson, Judith, and Deborah; Alexander and Caesar; Henry V and Joan of Arc; Thomas More, Lady Jane Grey, and Mary Queen of Scots; Elizabeth I and Walter Raleigh; George Washington, the Duke of Wellington, and Lord Nelson; Emily Dickinson; Abraham Lincoln and Robert E. Lee; Winston Churchill and Charles de Gaulle; Mae West and Marilyn Monroe; Ronald Reagan, Margaret Thatcher, and Pope John Paul II.
Keywords: Heroes -Biography.